ANALISIS MAKNA PERIBAHASA JEPANG YANG MENGGUNAKAN UNSUR IKAN - Jumia Elvita Elvita; Hana Nimashita Nimashita; Yenny Aristia Nasution Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study examines the analysis of the Japanese proverb meaning that use fish element. Fish itself are not only used as a food ingredient in Japan, but there are also values its philosophy. The purpose of this study was to find out what the Japanese proverb meaning that using fish elements and knowing how Japanese people view against the fish in terms of the Great Chain Metaphor Theory.This study used qualitative descriptive method.It finds that the use of fish element such as Seabreams, koi, eel, and mackerel in Japanese proverb and explain the things that led to the use of fish elements. In addition, it also to find out the function of proverb that use of fish elements.Data obtained from books, dictionaries, journals, theses related to these proverbs and uses semantic cognitive theory and the theory named with The Great Chain Metaphor Theory. Results from this study indicate that the fish is not only have meaning as carriers of luck, but there are also a variety of cultures, and the myth that contained in it. KeyWord:CognitiveSemantics, The Great Chain Metaphor Theory, Fish Elements, Japanese Proverb